Informe sobre una población de híbridos de Urochloa (Bh16) y su información asociada, entregado al sector privado para pruebas y difusión en múltiples entornos - Hernández, Luis Miguel; Mazabel, Johanna; Ríos, Gonzalo; Castiblanco, Valheria (Bioversity International and the International Center for Tropical Agriculture, 2021)
The aim of this report is to summarize the information concerning to different evaluations performed on the hybrid population Bh16 conformed by 27 genotypes, which were qualified as superior and selected from an initial cohort of 3050 hybrids. We present the results obtained from evaluations of i) resistance to biotic stress imposes by the spittlebug A. varia (Hemiptera: Cercopidae); ii) progeny test to corroborate previous results with molecular markers; and iii) an agronomic comparison against two commercial cultivars (cv Llanero and cv Tully). We discuss the results obtained in each evaluation and the proposal of the following stages to continue in the selection process of the best 10 Bh16 hybrids.